2012
DOI: 10.1002/anie.201207063
|View full text |Cite
|
Sign up to set email alerts
|

DNA Aptamer‐Mediated Cell Targeting

Abstract: One important issue using cells as therapeutics is targeted delivery. Engineering cell surfaces to improve delivery efficiency is thus of great interest. Here we report a simple, efficient and effective way to modify the cell surface with target-specific ligands, i.e., DNA aptamers, while minimizing the effects on the modified cells. We demonstrated that after incubating with lipo-aptamer probes (shown in expansion), immune cells (red) recognize cancer cells (blue) in the cell mixture, and kill cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
155
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(156 citation statements)
references
References 36 publications
1
155
0
Order By: Relevance
“…For example, catalytic beacons [20][21][22] and structure-switching aptamers [23][24][25][26][27] have been developed as DNAzyme-and aptamer-based fluorescent biosensors, respectively, for the detection of a broad range of targets. In addition, functional DNA sensors have been successfully applied for the imaging of metal ions [28], molecules inside live cells [29][30][31] and surfaces of cancer cells [32][33][34], suggesting their great promise for target detection in highly complex environment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, catalytic beacons [20][21][22] and structure-switching aptamers [23][24][25][26][27] have been developed as DNAzyme-and aptamer-based fluorescent biosensors, respectively, for the detection of a broad range of targets. In addition, functional DNA sensors have been successfully applied for the imaging of metal ions [28], molecules inside live cells [29][30][31] and surfaces of cancer cells [32][33][34], suggesting their great promise for target detection in highly complex environment.…”
Section: Introductionmentioning
confidence: 99%
“…The diacyllipid-DNA conjugate, which was first synthesized in our lab, was prepared by directly incorporating a diacyllipid phosphoramidite tail on the 5′-end of the DNA sequence in an automated DNA synthesizer [61]. We have demonstrated that the diacyllipid-DNA conjugate can efficiently self-assemble onto the cell membrane based on the hydrophobic interaction between the lipophilic tail and the cellular phospholipid layer [61,62]. The membrane-anchored DNA biosensors could be simply fabricated by directly incubating the cells with the diacyllipid-DNA probes and then washing away the free probes.…”
Section: Building Dna Biosensors On Target Living Cell Surfacesmentioning
confidence: 99%
“…[2][3][4] In recent years, various (bio-)chemical approaches have been reported to functionalize and/or derivatize the cell membrane with various components including nucleic acids, [5][6][7] peptides, 8 synthetic polymers [9][10][11] and nanoparticles [12][13][14][15] for cell therapy. CSR is particularly useful in the construction of 3D cell/tumour spheroids, and cellbiomaterial ensembles for tissue engineering applications as the concentration of the synthetic component, i.e.…”
mentioning
confidence: 99%